Turkish Publications in SCI/SCI-E Indexed Journals in the Field of Intensive Care: A Bibliographic Analysis - Sibel Büyükçoban; Volkan Hancı; Şule Özbilgin; Düriye Gül İnal (Galenos Yayinevi, 2024)
Objective: Our study aimed to evaluate publications originating from Turkey in the field of "intensive care" in the journals with Science Citation index (SCI) and SCI-Expanded (SCI-E). Materials and Methods: Journals related to "Intensive Care" in the SCI-E database of "Thomson Reuters Web of Science" were scanned. The Institute for Scientific Information Web of Science search engine was used in advanced mode by typing "IS = ISSN number" to identify publications in the journal. By typing "IS = ISSN number and CU = Turkey", articles related to intensive care originating from Turkey were found. Mann-Whitney U test was used to statistically evaluate the percentages and annual averages of publications in journals originating from Turkey and grouped according to different criteria. The relationship between the impact factors of the journals and the percentage and annual publication average of publications originating from Turkey was analyzed with the Pearson correlation test. A p value of less than 0.05 was considered a significant difference. Results: According to the percentage of publications in the field of intensive care, the three journals with the highest publications originating from Turkey were determined as "Burns", "Journal of Burn Care & Research", "Journal of Critical Care". While Turkey ranked 22nd between 1975 and 2021, it rose to 19th place in the last decade and the last five years. The total number of publications originating from Turkey, the average number of annual publications and the percentage of publications are significantly higher in journals published in English than in journals published in other languages (p<0.05). Conclusion: The article with the highest rate from Turkey in the field of intensive care was published in the journals "Burns", "Journal of Burn Care & Research", "Journal of Critical Care". While our country is not behind other countries in terms of the number of intensive care beds and workforce, as seen during the coronavirus disease period, it is lagging behind in the field of intensive care publication; It should be an academic driving force.